Amount of Easily Soluble Salts in Water, Type and Level of Salinity in Irrigated Meadow-Gray Soils of Zomin Cone Spread and Its Effect on Soil Melioration - Kholboev Bahromjon Ernazarovich (Zien Journals, 2022)
The article describes the results of scientific research on the effective use of irrigated soils of the Zomin cone spread. The results of statistical analysis on the amount of easily soluble salts in water in the irrigated meadow-grey soils of the Zomin cone spread, the depth of the saline layer, its thickness and the degree of salinity are presented.
Keywords: Zomin cone spread; salinity; high salinity; profile salinity